66.3k views
4 votes
Explain how do you do it If you put only the answer i will report you

Explain how do you do it If you put only the answer i will report you-example-1
Explain how do you do it If you put only the answer i will report you-example-1
Explain how do you do it If you put only the answer i will report you-example-2

1 Answer

3 votes

Answer:


d = √(113) = 10.63014

Explanation:

Distance between the endpoints of the graph, (-3, 3) and (5, -4), can be calculated using distance formula,
d = √((x_2 - x_1)^2 + (y_2 - y_1)^2).

Where,


(-3, 3) = (x_1, y_1)


(5, -4) = (x_2, y_2)

Thus,


d = √((5 - (-3))^2 + (-4 - 3)^2)


d = √((8)^2 + (-7)^2)


d = √(64 + 49) = √(113)


d = √(113) = 10.63014

User Arjjun
by
4.6k points